Une relecture de l'arrêt Matamajaw Salmon Club - Normand, Sylvio (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
The case of Matamajaw Salmon Club v. Duchaine1 certainly remains one of the notorioustly outstanding decisions on a civil law issue handed down by the Privy Council. For many, the decision seems difficult to reconciliate with the civil law concept of ownership. None the less, most authors and judges attempt to minimize the incoherency. Here the decision is first presented and then the ration decidendi is analysed while its impact on the concept of property is considered.